2022
DOI: 10.12688/f1000research.126301.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a pulmonary rehabilitation program on social disadvantage and physical activity data of postCOVID19 patients: A North-African pilot study

Abstract: Background In addition to the cardiorespiratory, muscular, and neurological manifestations, coronavirus disease 2019 (COVID-19) alters patients’ health-related quality of life (HRQoL), induces a large variety of psychiatric manifestations, and reduces mobility and motor activity. Several studies have raised the impact of a pulmonary rehabilitation program (PRP) on social disadvantage (e.g., HRQoL, anxiety, depression) and physical activity of COVID-19 patients, but very few have been performed in low-income c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
(204 reference statements)
1
2
0
Order By: Relevance
“…This finding may be attributed to the effect of Covid-19 on the respiratory system that affect lung tissue and decrease o2 saturation so, patients complain from extreme fatigue.Additionally, this improvement may be due to the effect of the rehabilitation program via using the information technology such as (whatsapp text messaging, video, and audio calls ) , most of telerehablitation group were health care provider and highly educated in addition to, using the traditional colored educational booklet with clear, attractive and simple written information and sending the colored educational photo and recorded video to the studied group. Moreover, this finding was in consistence with Graham (2021) (42) and de Sire (2022) (42) who reported that the most of post covid-19 patients experienced fatigue. Meanwhile, in telehealth group one month after implementing the pulmonary rehabilitation program the finding was in agreement with Bickton (2021) (41) who reported that the fatigue score was decrease to normal fatigue level in post-acute COVID-19 who utilized the qualified physiotherapist's supervision via whatsapp text messaging, video and audio calls for (telerehablitation ) for 3 weeks.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This finding may be attributed to the effect of Covid-19 on the respiratory system that affect lung tissue and decrease o2 saturation so, patients complain from extreme fatigue.Additionally, this improvement may be due to the effect of the rehabilitation program via using the information technology such as (whatsapp text messaging, video, and audio calls ) , most of telerehablitation group were health care provider and highly educated in addition to, using the traditional colored educational booklet with clear, attractive and simple written information and sending the colored educational photo and recorded video to the studied group. Moreover, this finding was in consistence with Graham (2021) (42) and de Sire (2022) (42) who reported that the most of post covid-19 patients experienced fatigue. Meanwhile, in telehealth group one month after implementing the pulmonary rehabilitation program the finding was in agreement with Bickton (2021) (41) who reported that the fatigue score was decrease to normal fatigue level in post-acute COVID-19 who utilized the qualified physiotherapist's supervision via whatsapp text messaging, video and audio calls for (telerehablitation ) for 3 weeks.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, Gilmutdinova (2021) (41) who stated that the well-being improved in the majority of patients who participated in an intervention involving telerehabilitation and telemonitoring after COVID-19. Also, Betschart (2021) (33) and Benzarti (2022) (42) who reported that there was a statistically significant improvement in HRQoL from more than half before the program to the majority after implementing the program in Vol. 28.…”
Section: Discussionmentioning
confidence: 99%
“…Benzarti et al studied the outcome of a pulmonary rehabilitation program in 14 patients with moderate to severe post-COVID symptoms. 13 They used questionnaires for health-related quality of life, depression, anxiety, and physical activity. The rehabilitation program involved three sessions per week for four weeks.…”
Section: Nopp Et Al Reported a Prospective Cohort Observational Study...mentioning
confidence: 99%